EFFECTIVENESS OF WARM SALT WATER SOAKING FOR JOINT PAIN IN THE ELDERLY WANT JAYA DISTRICT, ACEH BESAR, INDONESIA - Rehmaita Malem; Andry Nazarra; Aina Fitri; Mulia Putra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The elderly are a group or population at high risk of experiencing health problems. Health problems often experienced by the elderly are caused by decreased function of the body's systems. This research aims to determine the effectiveness of education on joint pain management through complementary therapy in older people based on warm salt water soaking videos. This research is a research with a one-group pretest-posttest design. The population in this study was 37 older adults who experienced joint pain. The sampling technique uses a total sampling technique. Soak in warm salt water once by dipping your feet and soaking your feet 10-15 cm above the ankles for 15 minutes. The water temperature used is 32°C-35°C. The study results showed that educational actions were effective in treating joint pain through complementary therapy in older people based on videos of warm salt water immersion (P=0.000). Soaking feet in salt water can be an alternative therapy for older adults with joint pain.